2013
DOI: 10.1371/journal.pone.0050036
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Morbidity in High and Seasonal Malaria Transmission Area of Burkina Faso

Abstract: BackgroundMalariometric parameters are often primary endpoints of efficacy trials of malaria vaccine candidates. This study aims to describe the epidemiology of malaria prior to the conduct of a series of drug and vaccine trials in a rural area of Burkina Faso.MethodsMalaria incidence was prospectively evaluated over one year follow-up among two cohorts of children aged 0–5 years living in the Saponé health district. The parents of 1089 children comprising a passive case detection cohort were encouraged to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 16 publications
(17 reference statements)
14
34
1
Order By: Relevance
“…Malaria-related immunosuppression could lead to reduced vaccine immunogenicity or differences in innate immunity may exist in the early weeks of life in these children. Congruently, malaria transmission in the Gambia is markedly lower than in Burkina Faso,37, 39, 41 thus these effects would likely be seen in older Gambian children who have had more years of lower level malaria exposure; and in younger infants in Burkina Faso where transmission is higher 42, 43…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria-related immunosuppression could lead to reduced vaccine immunogenicity or differences in innate immunity may exist in the early weeks of life in these children. Congruently, malaria transmission in the Gambia is markedly lower than in Burkina Faso,37, 39, 41 thus these effects would likely be seen in older Gambian children who have had more years of lower level malaria exposure; and in younger infants in Burkina Faso where transmission is higher 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical trials were performed in the western region of The Gambia in Sukuta, where modest malaria transmission is still observed following seasonal rains, despite a substantial decline in incidence since 2003 37 . A third study was undertaken in Burkina Faso with highly seasonal transmission and a far greater incidence of malaria than in The Gambia, averaging more than one confirmed clinical episode per child per year 38, 39. An effective malaria vaccine would be useful in both settings.…”
Section: Introductionmentioning
confidence: 99%
“…Olutu et al (2010) in Kenya [11], found that incidence was three times as high with active compared to passive detection; they found both methods had high specificity provided fever was determined by measurement rather than reported history. We found only one randomized comparison, Ouedraogo et al (2013) [8]. They compared the two methods in a randomized trial; incidence was higher in the active arm but they did not compare the severity of malaria cases.…”
Section: Introductionmentioning
confidence: 92%
“…The entomologic inoculation rate was estimated at 200 infective bites/person/year in the study area [17]. The incidence of clinical malaria cases in children less than five years of age was estimated at 1.3 episodes/child-year [18]. …”
Section: Methodsmentioning
confidence: 99%